Use of a Potential Probiotic, Lactobacillus plantarum L7, for the Preparation of a Rice-Based Fermented Beverage - Giri, Sib Sankar; Sen, Shib Sankar; Saha, Subrata; Sukumaran, Venkatachalam; Park, Se Chang (Frontiers in Microbiology, 2018)
This study aimed to isolate potential probiotic lactic acid bacteria from a traditional rice-based fermented beverage “bhaati jaanr” and to evaluate their role during preparation of the beverage. Among various isolates, Lactobacillus plantarum strain L7 exhibited satisfactory in vitro probiotic characteristics such as acid resistance and bile tolerance, cell surface hydrophobicity, auto-aggregation, antibiotic susceptibility, and antimicrobial activities. Therefore, performance of L7 as a starter culture in rice fermentation was determined during a 6-day rice fermentation study. L. plantarum L7 decreased the pH, associated with an increase in total titratable acidity and organic acid production up to the 4th day of fermentation. The highest concentrations of succinic acid (0.37 mg/g), lactic acid (4.95 mg/g), and acetic acid (0.36 mg/g) were recorded on the 3rd, 4th, and 5th days of fermentation, respectively. Saccharifying (148.13 µg/min g-1) and liquefying (89.47 µg/min g-1) activities were the highest on days 3 and 2, respectively, and thereafter, they decreased. Phytase activity and the cleavage of free minerals (sodium, calcium, magnesium, manganese, and ferrous) increased up to days 3–4. The concentration of various accumulated malto-oligosaccharides (glucose, fructose, maltotriose, and maltoterose) was noted to be the maximum on days 4 and 5. Furthermore, gas chromatography-mass spectrometry analysis indicated the presence of various volatile compounds. The fermented material also exhibited 1,1-diphenyl-2-picrylhydrazyl and 2,2′-azino-bis(3-ethylbenzothiazoline-6-sulphonic acid) radical scavenging activity. Therefore, the probiotic, L. plantarum L7, has a significant role in the fermentation of this beverage and enhances its functional properties.